The Influence of Customer Experience, Customer Satisfaction, and Word of Mouth on Customer Loyalty at PT Aliyah Transport Batam - Riri Afrijannah; Asron Saputra (Journal of Social Research, 2026)
This research aims to analyze the extent to which customer experience, customer satisfaction, and word of mouth play a role in shaping customer loyalty at PT Aliyah Transport Batam. The approach used in this study is quantitative with a descriptive research type. The study population includes 251 customers who have used PT Aliyah Transport Batam’s transportation services, with a sample size of 154 respondents determined through purposive sampling techniques and referring to Slovin’s calculations to ensure sample adequacy. Data were collected using a structured questionnaire instrument, which was then analyzed through validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using t-tests and F-tests. The results of the analysis show that customer experience contributes 29.2% to customer loyalty at PT Aliyah Transport Batam. Furthermore, customer satisfaction influences 42.2%, while word of mouth contributes 53.1%. The coefficient of determination (R²) value of 91.7% indicates that the three variables simultaneously explain most of the variation in customer loyalty. The t-test and F-test findings confirm that, both partially and simultaneously, customer experience, customer satisfaction, and word of mouth significantly influence customer loyalty. This research concludes that customer experience, customer satisfaction, and word of mouth are critical determinants of customer loyalty at PT Aliyah Transport Batam, with word of mouth being the most dominant factor.